PENDAMPINGAN HAFALAN AL-QUR’AN DAN ARTINYA DENGAN METODE ILUSTRASI DI DUSUN SENTONO, KLATEN, JAWA TENGAH - Jamalul Lail (Asian Journal of Innovation and Entrepreneurship, 2015)
There are many ways in memorizing the Qur'an. One of the easiest is by usingillustrations and began when they are kids. Community service programs implemented to train the children memorize the Qur'an by the method of illustration in childrenSentono village, Klaten, Central Java.